1984
DOI: 10.1152/ajpregu.1984.247.2.r374
|View full text |Cite
|
Sign up to set email alerts
|

Rat organum vasculosum laminae terminalis in vitro: responses to transmitters

Abstract: Spontaneous single-action potentials (units) were recorded extracellularly from explants of the rat organum vasculosum laminae terminalis in vitro. Increasing the osmotic pressure of the bathing solution by 15% by adding NaCl or mannitol increased frequency, whereas reducing the osmotic pressure by 15% by omitting NaCl reduced frequency. The mean frequency ratio (test/control) for 6 (of 13) units responding to a 15% increase was 2.2 +/- 0.5 (SE), and for 8 (of 11) units responding to a 15% decrease it was 0.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…Support for this argument can be derived from morphological evidence that the median pre optic nucleus receives an innervation from the SFO [25] which may be angiotensinergic in part [18]. Finally, electrophysiological evidence indicates that neurons within the SFO, OVLT and nucleus medianus are sensitive to ANG 11 [17,[26][27][28]31]. Thus, based on the extensive physiological evidence regarding the effects of ANG II in this region, we believe (hat the [l25I]-sar'.ile8-ANG II binding sites demon strated within the SFO, median preoptic nucleus and OVLT represent labeling of the physiological ANG II receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Support for this argument can be derived from morphological evidence that the median pre optic nucleus receives an innervation from the SFO [25] which may be angiotensinergic in part [18]. Finally, electrophysiological evidence indicates that neurons within the SFO, OVLT and nucleus medianus are sensitive to ANG 11 [17,[26][27][28]31]. Thus, based on the extensive physiological evidence regarding the effects of ANG II in this region, we believe (hat the [l25I]-sar'.ile8-ANG II binding sites demon strated within the SFO, median preoptic nucleus and OVLT represent labeling of the physiological ANG II receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Only a small number of these cells were tested for osmosensitivity but two of the four OD + cells were excited by the osmotic stimulus and two of the three OD-cells were inhibited. (Thrasher, Keil & Ramsay, 1982), cells in the region are osmosensitive (Sayer et al 1984) magnocellular neurosecretory cells (Honda et al 1987), it is reasonable to suggest that osmosensitive elements in the AV3V region provide osmotic drive to the supraoptic nucleus. The present investigation was undertaken to provide electrophysiological evidence for such a direct connection between the two regions.…”
Section: Recordings From Cells In the A V3v Regionmentioning
confidence: 99%
“…In mammals, the primary osmosensory neurons mediating this task are located in the brain's organum vasculosum lamina terminalis (OVLT) (Thrasher et al, 1982;Ramsay et al, 1983;Johnson and Gross, 1993). Studies in rodents have shown that the rate of action potential discharge in osmosensitive OVLT neurons rises proportionally with extracellular fluid osmolality (Sayer et al, 1984;Honda et al, 1990;Vivas et al, 1990;Ciura and Bourque, 2006). Information encoded by this activity is relayed synaptically to effector nuclei to induce autonomic (Brooks et al, 2005), behavioral (Hollis et al, 2008), and neuroendocrine responses (Richard and Bourque, 1995;Trudel and Bourque, 2010) that maintain fluid homeostasis.…”
Section: Introductionmentioning
confidence: 99%